On Historical Regression: A Note at the Occasion of the 170th Anniversary of the Manifesto - Močnik, Rastko (Sociološki pregled, 2018)
Limitations of the Manifesto (absence of the concept of “social formation”; capitalism as “homofcient”) are treated as symptoms of a certain lefist theory with important practical political consequences. Tey are related to the defciencies of the Yugoslav critical lef (the belief that socialist revolution is irreversible; the underestimation of the main contradiction of post-capitalism: “capitalist processes / socialist processes and practices”) that prevented Yugoslav lefists adequately to confront the restauration of capitalism.